Increasing Inclusive Education Through a Learning Center Model: A California Approach (Journal of Education and Development, 2020)
Learning center models offer students with disabilities learning experiences in general education classrooms, while retaining support and services from special education personnel. The learning center approach examines existing educational perspectives, practices and structures, surrounding access to general education for students with disabilities. This study used a document analysis, a qualitative data method, to examine how two California school districts developed a learning center model to transform special education programming from segregated special education classrooms and practices to placement and access to general education. The findings inform educational programming for students with disabilities in the least restrictive environment, to comply with the American federal mandate. Findings suggest that the deep structure of educational practices complicated the ease of a change in practices for both general and special educators. However, the community approach of the learning center model, where all teachers assume the educational responsibilities for all students, forced these educators to be flexible, reexamine structures and practices, and challenge the ethos of traditional schooling.